1991
DOI: 10.3109/03005369109076614
|View full text |Cite
|
Sign up to set email alerts
|

The influence of contralateral acoustic stimulation on click-evoked otoacoustic emissions in humans

Abstract: Contralateral acoustic stimulation has the effect of reducing the amplitude and shifting the phase of click-evoked OAEs. This effect is thought to be mediated via the medial efferent system and, therefore, the presence of this effect could be used to test the integrity of the neural pathway from one cochlea to the other. With a clinical application in mind, a technique for demonstrating the influence of contralateral acoustic stimulation on click-evoked OAEs was designed to overcome fluctuations in patient and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0
5

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 10 publications
5
30
0
5
Order By: Relevance
“…Investigators have turned their attention to the study of the effects of contralateral stimuli on various parameters of evoked otoacoustic emissions in humans and in £uiimals and have demonstrated that stimulation of the ear opposite the one receiving the evoking stimulus reduces the amplitude of the otoacoustic emission (Berlin, Hood, Cecola, Jackson, & Szabo, 1993a;Berlin et al, 1994;Berlin et al, 1993b;Collet et al, 1990;Collet et al, 1992;Harrison & Bums, 1993;Kujawa, Glattke, Fallon, & Bobbin, 1992;Puel & Rebillard, 1990;Ryan, Kemp, & Hinchcliffe, 1991;Veuillet, Collet, & Duclaux, 1991). This effect is believed to be mediated by the MOC system (Berlin et al, 1994;Collet, 1993;Collet et al, 1990;Giraud, Collet, Chery-Croze, Magnan, & Chays, 1995), and suggests that the contralateral suppression of auditory nerve responses described previously may result from activity at the cochlear level.…”
Section: Suppression Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigators have turned their attention to the study of the effects of contralateral stimuli on various parameters of evoked otoacoustic emissions in humans and in £uiimals and have demonstrated that stimulation of the ear opposite the one receiving the evoking stimulus reduces the amplitude of the otoacoustic emission (Berlin, Hood, Cecola, Jackson, & Szabo, 1993a;Berlin et al, 1994;Berlin et al, 1993b;Collet et al, 1990;Collet et al, 1992;Harrison & Bums, 1993;Kujawa, Glattke, Fallon, & Bobbin, 1992;Puel & Rebillard, 1990;Ryan, Kemp, & Hinchcliffe, 1991;Veuillet, Collet, & Duclaux, 1991). This effect is believed to be mediated by the MOC system (Berlin et al, 1994;Collet, 1993;Collet et al, 1990;Giraud, Collet, Chery-Croze, Magnan, & Chays, 1995), and suggests that the contralateral suppression of auditory nerve responses described previously may result from activity at the cochlear level.…”
Section: Suppression Effectsmentioning
confidence: 99%
“…The suppression effect on evoked otoacoustic emissions in humans is a small but consistent decrease of 1-4 dB in overall emission amplitude in the presence of a contralateral acoustic stimulus (Berlin et al, 1993b(Berlin et al, , 1994Collet et al, 1990Collet et al, , 1992Ryan et al, 1991Ryan et al, , 1996Veuillet et al, 1991;Veuillet, Duverdy-Bertholon, & Collet, 1996). Collet is credited as the first person to describe contralateral suppression of evoked otoacoustic emissions in humans (Berlin et al, 1993b;Collet et al, 1990).…”
Section: Suppression Effectsmentioning
confidence: 99%
“…This suppression effect was noticed by numerous authors such as the reduction in the response level of spontaneous and evoked otoacoustic emissions with the use of contralateral acoustic stimulation 2,3 . Ryan et al 3 reported that contralateral acoustic stimulation reduces TEOAE amplitude. This phenomenon may be mediated by the medial olivocochlear efferent system and, thus, its presence may be used to assess the integrity of the neural communication from one cochlea to another.…”
Section: Introductionmentioning
confidence: 67%
“…The function of the MOCB can be investigated by measuring otoacoustic emissions (OAE). The amplitude of OAE can be reduced by contralateral acoustic stimulation (Warren and Liberman 1989;Collet et al 1990;Ryan et al 1991;Berlin et al 1993b), which is described as OAE suppression effect. This OAE suppression is related to speech understanding in noise (Kumar and Vanaja 2004) and is diminished (or even absent) in patients with speech in noise understanding impairments (Berlin et al 1993a;Starr et al 1996).…”
Section: Discrimination Deficits and Possible Top-down Engagementmentioning
confidence: 99%